Temperature and concentration dependent viscosity of microcrystalline cellulose in water - Shahrul Kadri Ayop (Tanjung Malim, 2021)
Temperature and concentration dependent viscosity of microcrystalline cellulose in water by Shahrul Kadri Ayop